Th e influence of European models on Russian monumental painting of the Synodal period as it is seen in churches of the Tver region - Surova, Anna A. (Actual Problems of Theory and History of Art, 2012)
The article is dedicated to cult murals of Tver region from the late 18th to early 20th c. painted after European originals: illustrated Bibles with engravings, replication and allegorical engravings. A lot of models and some peculiarities in using these models are studied basing on several surviving monumental complexes. Th e problem has not been studied well enough; the greater part of the material is introduced in the scientific span for the first time.